Multiple myeloma metabolism – a treasure trove of therapeutic targets? - Roman-Trufero, Monica; Auner, Holger W.; Edwards, Claire M. (Frontiers in Immunology, 2022)
Multiple myeloma is an incurable cancer of plasma cells that is predominantly located in the bone marrow. Multiple myeloma cells are characterised by distinctive biological features that are intricately linked to their core function, the assembly and secretion of large amounts of antibodies, and their diverse interactions with the bone marrow microenvironment. Here, we provide a concise discussion of major metabolic hallmarks of plasma cells and myeloma cells, their roles in myeloma development and progression, and how they could be exploited for therapeutic purposes. We review the role of glucose consumption and catabolism, assess the dependency on glutamine to support key metabolic processes, and consider metabolic adaptations in drug-resistant myeloma cells. Finally, we examine the complex metabolic effects of proteasome inhibitors on myeloma cells and the extracellular matrix, and we explore the complex relationship between myeloma cells and bone marrow adipocytes.